2020
DOI: 10.1021/acs.analchem.0c02104
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Effective Surface Area, Mass Transport, and Electrochemical Features in Nanoporous Nucleic Acid Sensors

Abstract: Four different film thicknesses of np-Au were sputtered using Lesker Labline Sputter System. For each of the sets, piranha-cleaned glass coverslips were sputter-coated with 160 nm-thick Cr layer to serve as an adhesive layer between the glass substrate and 80 nm-thick seed layer of Au. Ag and Au were co-sputtered on top of the Au-seed layer to obtain 36% Au and 64% Ag (atomic %) alloy 1. Alloy co-sputtering time was varied to allow for fabrication of varying film thicknesses (t = 5, 10, 20 and 30 min). All met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 67 publications
2
30
0
Order By: Relevance
“…The increase in the EAB signal we observe is smaller than the 75-to 100-fold increase in the microscopic surface area seen for nanoporous electrodes (Figure 2). This discrepancy, which is consistent with recent observations by Vesilinovic et al, who examined the impact of nanoporous gold surfaces on the signaling of a different class of electrochemical biosensors, 24 may result from two sources. First, hindered diffusion of the aptamer into the smallest pores in the matrix might reduce the number of aptamers per unit of the microscopic surface area.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in the EAB signal we observe is smaller than the 75-to 100-fold increase in the microscopic surface area seen for nanoporous electrodes (Figure 2). This discrepancy, which is consistent with recent observations by Vesilinovic et al, who examined the impact of nanoporous gold surfaces on the signaling of a different class of electrochemical biosensors, 24 may result from two sources. First, hindered diffusion of the aptamer into the smallest pores in the matrix might reduce the number of aptamers per unit of the microscopic surface area.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Because it allows the attachment of more aptamers to an electrode of a given size, increasing the microscopic surface area of the gold provides a route toward smaller EAB sensors. To this end, many techniques exist that enhance the microscopic surface area of gold, including a number of electrochemical etching/deposition approaches, co-sputtering, or the leaching of commercially available gold alloy foils. ,, Co-sputtering and the leaching of gold foil, however, are incompatible with the wire format of our implantable sensors. In contrast, electrochemical surface area enhancement techniques are readily compatible with our sensor architecture.…”
mentioning
confidence: 99%
“…This packing density is much lower than that of the commonly used macroelectrodes . The decrease in packing density at aptamer-modified nanoporous surfaces has been previously investigated by Veselinovic et al In their study, they demonstrated that the hindered diffusion of aptamers to smaller pores in a nonporous surface decreased the packing density . For our sensors, the lower packing density might be explained by the slower diffusion of aptamers near dendrite junctions.…”
Section: Results and Discussionmentioning
confidence: 47%
“…electrochemical processes on NPG films with small pore size has already been reported. [29][30] Interestingly, a different behavior was noticed in similar plots obtained for the AA electrode process for NPG films prepared at a fixed E D (-4 V) but for varying t D (in the range of 50 to 600 s) (Figure 7). At the shorter t D value (50 s), E 1/2 is reported instead of E p because the voltammogram recorded with this electrode presented a steady-state feature instead of a peak-shaped profile.…”
Section: Figurementioning
confidence: 73%
“…This has also been demonstrated in the recent work of Veselinovic et al, according to which the sensitivity for nucleic acid detection was not linearly proportional to the NPG electrochemical surface area (ECSA). [29] Therefore, a trade-off between mass transport limitation and ECSA is always noticed to improve the electroanalytical performance of NPG-based platforms. [30] This balance depends on two important factors: the kinetics and mechanism of the electrode reactions, and the pore size in the NPG films.…”
Section: Introductionmentioning
confidence: 99%